2007
DOI: 10.1254/jphs.fp0070122
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective and Antioxidant Effects of Montelukast on Indomethacin-Induced Gastric Ulcer in Rats

Abstract: Abstract. Montelukast, a selective reversible cysteinyl leukotriene D 4 -receptor (LTD 4 receptor) antagonist, is used in the treatment of asthma. We have investigated alterations in the glutathione (GSH) and activity levels of antioxidative enzymes [superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), and glutathione reductase (GR)] and myeloperoxidase (MPO), as markers of the ulceration process following oral administration of montelukast, lansoprazole, famotidine, and ranitidine, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 53 publications
5
64
0
3
Order By: Relevance
“…It is well known that CP leads to a significant reduced antioxidant status in humans and animals. 45,46 On the other hand, in another study, Dengiz et al 47 reported that montelukast plus CP injection generally reversed the toxic effects of CP and numerically increased GSH levels. Similarly here, montelukast administration could not increase reduction of GSH levels, whereas montelukast therapy tended to ameliorate GSH enzymes to nearly the same level as controls.…”
Section: Discussionmentioning
confidence: 96%
“…It is well known that CP leads to a significant reduced antioxidant status in humans and animals. 45,46 On the other hand, in another study, Dengiz et al 47 reported that montelukast plus CP injection generally reversed the toxic effects of CP and numerically increased GSH levels. Similarly here, montelukast administration could not increase reduction of GSH levels, whereas montelukast therapy tended to ameliorate GSH enzymes to nearly the same level as controls.…”
Section: Discussionmentioning
confidence: 96%
“…Neutrophil infiltration into the gastric mucosal tissues is a critical process in the pathogenesis of a variety of gastric ulcers. A relationship between the anti-oxidant and anti-ulcerogenic effects of montelukast was shown in our previous study (13). The purpose of the present study was to investigate the relationship between the gastroprotective effect of montelukast and polymorphonuclear leukocytes (PMNL) infiltration in the gastric tissues.…”
Section: Introductionmentioning
confidence: 65%
“…We previously showed the anti-ulcerogenic and anti-oxidant activities of montelukast in the same ulcer model (13). In this study, we aimed to determine the relationship between the anti-ulcerogenic effects and PMNL infiltration into the gastric mucosa.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Numerous studies have shown that montelukast possesses considerable antioxidant and anti-inflammatory functions (16,25). Protective effects of montelukast against oxidative stress have been attributed to a neutrophildependent pathway, ROS scavenging properties and inhibition of caspase 3 (14,26,27).…”
Section: Discussionmentioning
confidence: 99%